Pelatihan Pembuatan Teks Pidato Dan Berpidato Pada Siswa Kelas XII Smk Semesta Bumiayu - Dwi Atmoko; Rosmalia Rosmalia; Agung Tyas Subekti (JABI: Jurnal Abdimas Bhakti Indonesia, 2020)
Speech is the expression of ideas from one person to another with oral delivery techniques. Someone who is good at speaking or giving speeches will easily be able to master the masses, and successfully market his ideas so that they can be accepted by others. Community service activities at Semesta Bumiayu Vocational School are aimed at: 1) providing knowledge in writing speech texts according to systematics, 2) providing knowledge about language rules, 3) and training in reading speech texts well. the implementation methods used in this service are: 1) lecture method, intended to deliver speech text training materials, 2) dialogic method, intended for question and answer and discussion about how to make speech texts using good and correct Indonesian, 3 ) training methods, intended to instill the skills and speaking skills using good and correct language. The training in writing speech texts and giving speeches in community service consists of three steps. The first step students get speech text material, the material delivered is the structure of the speech text. The second step students exercise to make the text of the speech, while the steps to compile the speech text: 1) Determine the theme, 2) Determine the purpose and purpose of the contents of the speech, 3) Gather material, 4) Making a framework, then developed into a complete speech script. The third step of the practice of giving speeches, when there are several obstacles encountered, one of them is lack of confidence, and not calm in reading the text of the speech, this is very reasonable because students rarely speak in public. To overcome this, regular training should be needed, so that students' confidence grows and improves properly.